Broccoli Microgreens: A Mineral-Rich Crop That Can Diversify Food Systems - Weber, Carolyn F. (Frontiers in Nutrition, 2017)
Current malnourishment statistics are high and are exacerbated by contemporary agricultural practices that damage the very environments on which the production of nutritious food depends. As the World’s population grows at an unprecedented rate, food systems must be revised to provide adequate nutrition while minimizing environmental impacts. One specific nutritional problem that needs attention is mineral (e.g., Fe, Zn) malnutrition, which impacts over two-thirds of the World’s people living in countries of every economic status. Microgreens, the edible cotyledons of many vegetables, herbs and flowers, is a newly emerging crop that may be a dense source of nutrition and has the potential to be in just about any locale. This study examined the mineral concentration of broccoli microgreens produced using compost-based and hydroponic growing methods that are easily implemented in one’s own home. The nutritional value of the resulting microgreens was quantitatively compared to published nutritional data for the mature vegetable. Nutritional data was also considered in the context of the resource demands (i.e., water, fertilizer, energy) of producing microgreens in order to gain insights into the potential for local microgreen production to diversify food systems, particularly for urban areas, while minimizing the overall environmental impacts of broccoli farming. Regardless of how they were grown, microgreens had larger quantities of Mg, Mn, Cu and Zn than the vegetable. However, compost-grown (C) microgreens had higher P, K, Mg, Mn, Zn, Fe, Ca, Na and Cu concentrations than the vegetable. For eight nutritionally important minerals (P, K, Ca, Mg, Mn, Fe, Zn, Na), the average C microgreen: vegetable nutrient ratio was 1.73. Extrapolation from experimental data presented here indicates that broccoli microgreens would require 158 to 236 times less water than it does to grow a nutritionally equivalent amount of mature vegetable in the fields of California’s Central Valley in 93-95% less time and without the need for fertilizer, pesticides or energy-demanding transport from farm to table. This study indicates that broccoli microgreens have the potential to be a rich source of minerals that can be produced by individuals, even in urban settings, providing better access to adequate nutrition.